Pencegahan Mastitis Subklinis Pada Sapi Perah dengan Menggunakan Bahan Herbal Sebagai Teat Dipping - Happy Aprillia Mahardika (Balai Pelatihan Pertanian Jambi, 2022)
Subclinical mastitis is a disease caused by bacteria. The mastitis cases in dairy cows can be prevented by doing teat dipping. This study was conducted to compile sufficient information about the prevention of mastitis in dairy cows using herbal ingredients in the form of cherry leaves, betel leaves, moringa leaves, basil leaves, and